Manajemen Disiplin Kerja dalam Meningkatkan Kinerja Guru - Muna Fauziah; Suryanti Suryanti; Sulis Rokhmawanto (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2021)
This study aims to analyze the management of work discipline in improving teacher performance. This research use desciptive qualitative approach. The subject of this research is the Head of Madrasah. The informants of this research are teachers. Data collection techniques using observation, interviews, and documentation. Check the validity of the data using triangulation of sources and methods. The data analysis technique uses an interactive analysis model, which consists of data reduction, data presentation, and drawing conclusions. The results of this study can be concluded that: at MTs Al Islamiyah Balorejo Bonorowo in applying preventive discipline to teacher performance has been carried out since the beginning of the establishment of MTs Al Islamiyah Balorejo Bonorowo, while corrective discipline is also carried out, but the punishment given is not so burdensome in the sense that it is still just reprimand. Meanwhile, corrective discipline at MTs Al Islamiyah Balorejo Bonorowo so far has only been used as a reference, a reference to make teachers even more disciplined. At MTs Al Islamiyah Balorejo Bonorowo in carrying out discipline obeying the rules and performance penalties are always applied because it is a rule that must be followed by all teachers and employees at MTs Al Islamiyah Balorejo Bonorowo in order to improve discipline.